Enhancing STEM Education in Early Childhood: Science Process Skills, Effective Questioning, and Science Concept Understanding of Kindergarten Teachers in Greater Bandung Area - Meidina Rizkita; Lintang Ratri Prastika; Apriyagung Apriyagung; Zuhe Safitra; Reza Setiawan (Universitas Negeri Semarang, 2026)
Aligned with Indonesia’s Education Roadmap 2025–2045 in improving Early Childhood Education (ECE) and promoting STEM learning in ECE to develop innovation and problem-solving skills in children from an early age, his study aims to examines the readiness of early childhood educators in the Greater Bandung area to implement STEM learning, focusing on three areas: science process skills (SPS), effective questioning, and science concept understanding. Utilizing a convergent parallel mixed-method design, data were collected from 17 purposively selected kindergartens through direct classroom observations, video and audio transcripts, and teacher interviews. The results show that kindergarten teachers in the Greater Bandung area demonstrate a